Responses of soil erosion to land‐use changes in the largest tableland of the Loess Plateau. (4th July 2021) - Zhang, Jianxiang; Wang, Naiang; Wang, Yafeng; Wang, Linhua; Hu, Aiping; Zhang, Duoyong; Su, Xianbao; Chen, Junhe
Abstract: Soil erosion is a global environmental problem, and land‐use changes have significantly altered soil erosion processes. However, soil erosion processes and their major influencing factors vary among different landforms. Dongzhiyuan (DZY), that is, the largest tableland in the Loess Plateau (LP), has experienced significant land‐use changes in previous decades. However, little is known about impacts of land‐use changes on soil erosion across different landforms in the DZY tableland. LANDSAT images from 1987, 1997, 2007, and 2017 were used to extract information on the land‐use changes in DZY. The decreases of farmland amount to 2.57 × 10 4  ha from 1987 to 1997, forest by 1.30 × 10 4  ha from 1997 to 2007, and grassland by 2.74 × 10 4  ha from 2007 to 2017. Urban areas increased by 1.41 × 10 4  ha from 1987 to 2017. The soil erosion estimated by the revised universal soil loss equation (RUSLE) and Chinese soil loss equation (CSLE) was 11.3 and 5.8 t ha −1 yr −1, respectively. The conversion from urban areas to farmland and grassland increased soil erosion. Changes from farmland to grassland and forest to grassland, intensified soil erosion; the severity of soil erosion depended on the intensity of the land‐use changes. Urban expansion caused a smaller decrease in soil erosion in the loess tableland, whereas vegetation restoration, to a large extent, decreased soil erosion in the loess gully area. Anthropogenic activity accelerated soil erosion before 1997, but slowed its influence after 1997. This study provides a reference for land‐use planning and soil water conservation in the LP.